Table of Contents

## Moufang loops

Abbreviation: **MLoop**

### Definition

A ** Moufang loop** is a loops $\mathbf{A}=\langle A,\cdot ,\backslash,/,e\rangle $ such that

$((xy)z)x = x(y(zx))$, $y(x(yz)) = ((yx)y)z$, $(yx)(zy) = (y(xz))y$

Remark:

##### Morphisms

Let $\mathbf{A}$ and $\mathbf{B}$ be Moufang loops. A morphism from $\mathbf{A}$ to $\mathbf{B}$ is a function $h:A\rightarrow B$ that is a homomorphism:

$h(xy)=h(x)h(y)$, $h(x\backslash y)=h(x)\backslash h(y)$, $h(x/y)=h(x)/h(y)$, $h(e)=e$

### Examples

Example 1:

### Basic results

### Properties

### Finite members

$\begin{array}{lr} f(1)= &1\\ f(2)= &\\ f(3)= &\\ f(4)= &\\ f(5)= &\\ f(6)= &\\ f(7)= &\\ \end{array}$

### Subclasses

### Superclasses

### References

Trace: » moufang_loops